Prevention of Chronic Rejection of Marginal Kidney Graft by Using a Hydrogen Gas-Containing Preservation Solution and Adequate Immunosuppression in a Miniature Pig Model - Nishi, Kotaro; Iwai, Satomi; Tajima, Kazuki; Okano, Shozo; Sano, Motoaki; Kobayashi, Eiji (Frontiers in Immunology, 2021)
In clinical kidney transplantation, the marginal kidney donors are known to develop chronic allograft rejection more frequently than living kidney donors. In our previous study, we have reported that the hydrogen gas-containing organ preservation solution prevented the development of acute injuries in the kidney of the donor after cardiac death by using preclinical miniature pig model. In the present study, we verified the impact of hydrogen gas treatment in transplantation with the optimal immunosuppressive protocol based on human clinical setting by using the miniature pig model. Marginal kidney processed by hydrogen gas-containing preservation solution has been engrafted for long-term (longer than 100 days). A few cases showed chronic rejection reaction; however, most were found to be free of chronic rejection such as graft tissue fibrosis or renal vasculitis. We concluded that marginal kidney graft from donor after cardiac death is an acceptable model for chronic rejection and that if the transplantation is carried out using a strict immunosuppressive protocol, chronic rejection may be alleviated even with the marginal kidney.